2010
DOI: 10.1167/iovs.09-5127
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Acutely Elevated Hydrostatic Pressure in a Rat Ex Vivo Retinal Preparation

Abstract: These results suggest that the neural degeneration observed during pressure elevation is caused by impaired glial glutamate metabolism after uptake.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
40
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(48 citation statements)
references
References 35 publications
8
40
0
Order By: Relevance
“…Nonetheless, Zhang et al reported that the induced expression of GS was observed as early as 24 h following the IOP in elevation in the rat models of acute intraocular hypertension (31). Ishikawa et al also reported that the pressure was associated with the GS activity in rat glaucomatous model in vivo (32). In our study, Western blotting and real-time PCR demonstrated that the expression of GS and GLAST was obviously increased at 40 mmHg pressure.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Nonetheless, Zhang et al reported that the induced expression of GS was observed as early as 24 h following the IOP in elevation in the rat models of acute intraocular hypertension (31). Ishikawa et al also reported that the pressure was associated with the GS activity in rat glaucomatous model in vivo (32). In our study, Western blotting and real-time PCR demonstrated that the expression of GS and GLAST was obviously increased at 40 mmHg pressure.…”
Section: Discussionsupporting
confidence: 69%
“…Holcombe et al reported that IOP threshold of ~70 mmHg for the maintenance of retinal perfusion and IOPs elevated ≤70 mmHg was consistent with the maintenance of GLAST activity in rat glaucomatous model in vivo (30), which was consistent with our result (40 mmHg pressure). Woldemussie et al found that the expression of GLAST increased and remained high for 2 months, following the elevation of IOP (30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40) in rat glaucomatous models in vivo, however, the expression of GS showed little change for the first 3 weeks (13). Nonetheless, Zhang et al reported that the induced expression of GS was observed as early as 24 h following the IOP in elevation in the rat models of acute intraocular hypertension (31).…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, Park et al [58] reported that the expression of GLT-1 was expressed in cone photoreceptors and the level of expression in some cone bipolar cells was significantly increased in in vivo glaucoma model. They also demonstrated that GLAST expression in Müller cells remained stable during the experimental period.…”
Section: B Glt-1mentioning
confidence: 86%
“…GLT-1, the main neuronal glutamate transporter in the retinal neurons, is reported to be downregulated in glaucomatous eyes in rats [58,66] and mice [57]. By contrast, Park et al [58] reported that the expression of GLT-1 was expressed in cone photoreceptors and the level of expression in some cone bipolar cells was significantly increased in in vivo glaucoma model.…”
Section: B Glt-1mentioning
confidence: 97%
See 1 more Smart Citation